Young asteroid families as the primary source of meteorites - Brož, M; Vernazza, P; Marsset, M; DeMeo, F E; Binzel, R P; Vokrouhlický, D; Nesvorný, D (Nature, 2024)
Understanding the origin of bright shooting stars and their meteorite samples is among the most ancient of astronomy-related questions, which at larger scales has human consequences1-3. As of today, only approximately 6% of meteorite falls have been firmly linked to their sources (Moon, Mars or asteroid (4) Vesta4-6). Here we show that approximately 70% of meteorites originate from three recent break-ups of D > 30 km asteroids that occurred 5.8, 7.6 and less than about 40 Myr ago. These break-ups, including the well-known Karin family7, took place in the prominent yet old Koronis and Massalia families and are at the origin of the dominance of H and L ordinary chondrites among meteorite falls. These young families are distinguished among all main belt asteroids by having a uniquely high abundance of small fragments. Their size-frequency distribution remained steep for a few tens of millions of years, exceeding temporarily the production of metre-sized fragments by the largest old asteroid families (for example, Flora and Vesta). Supporting evidence includes the existence of associated dust bands8-10, the cosmic-ray exposure ages of H-chondrite meteorites11,12 and the distribution of the pre-atmospheric orbits of meteorites13-15.